2004
DOI: 10.1182/blood.v104.11.1779.1779
|View full text |Cite
|
Sign up to set email alerts
|

Argatroban Dosage in Critically Ill Patients with HIT.

Abstract: Heparin-induced thrombocytopenia (HIT) is a serious complication of heparin therapy that can result in significant morbidity and mortality. Immediate discontinuation of heparin followed by the administration of a direct thrombin inhibitor (DTI) is the standard of care. There are two DTIs approved by the FDA for this indication, argatroban and lepirudin. Argatroban is metabolized in the liver by hydroxylation and aromatization and requires dosage adjustment in patients with moderate hepatic impairment defined a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2005
2005
2009
2009

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…This remains to be investigated further. Other reports suggest that a reduced initial dose, such as that recommended for patients with hepatic impairment (0.5 μg/kg/min), may be appropriate in critically ill patients who have multisystem organ failure (20) or who have decreased liver perfusion such as may occur following cardiothoracic surgery (21).…”
Section: Discussionmentioning
confidence: 99%
“…This remains to be investigated further. Other reports suggest that a reduced initial dose, such as that recommended for patients with hepatic impairment (0.5 μg/kg/min), may be appropriate in critically ill patients who have multisystem organ failure (20) or who have decreased liver perfusion such as may occur following cardiothoracic surgery (21).…”
Section: Discussionmentioning
confidence: 99%
“…The overall distribution of therapeutic argatroban dosages among our critically ill patients correlates with those described in previous case reports 11 -13,22 and studies. 14,15 Collectively, these data strongly suggest that critically ill patients require argatroban dosages well below those designated in current FDA-approved labeling. Prior to our findings, however, limited data were available to guide argatroban dosage decisions in patients with nonhepatic organ failure.…”
Section: Effects Of Critical Illness and Organ Failure On Argatroban mentioning
confidence: 94%
“…RÉSULTATS: Cinquante-trois patients ont été inclus dans l'étude (34 patients en état critique et 19 patients en état non-critique). Les patients critiques avaient un score médian pour l'échelle d'APACHE II (17 [12][13][14][15][16][17][18][19][20][21] comparativement 10 [3.25-17.75]; p = 0.007) et de 11 (7)(8)(9)(10)(11)(12)(13) comparativement à 2 (0-2.75); p < 0.001 pour le score de SOFA. Les patients en état critique ont reçu en moyenne une posologie moins élevée d'argatroban (0.6 ± 0.5 vs 1.4 ± 0.9 µg/kg/min; p < 0.001).…”
Section: Conclusionesunclassified
“…Other investigators have also reported low mean infusion rates for argatroban in patients with renal insufficiency. 123,124 Most of the available pharmacokinetic and pharmacodynamic data suggest that argatroban is not removed during hemodialysis. 125,126 However, one report noted a 20% increase in the systemic clearance of argatroban during intermittent hemodialysis in patients without HIT.…”
Section: Impaired Renal Hepatic or Cardiac Functionmentioning
confidence: 99%